Sustainability as a contribution to long-term success - Rocklage, Metje (Ökologisches Wirtschaften - Fachzeitschrift, 2018)
Is sustainability a contribution to long-term success? How does it work? Using the case of German graphic design industry businesses, this article explores the influence of sustainability as a contribution to long-term success.